Significance of Informal Trading Activities in The Emergence of Urban Spatial Vernacular: Case Study of Lagos Island, Nigeria - O. A, Onolaja; Jolaoso, Adekoyejo Babatunde (University of Merdeka Malang, 2021)
Informal trading activities such as street hawking and sedentary trade have assumed a prominent role in public space use in Lagos Island. They have contributed significantly to the Island’s built environment morphology as an urban commercial centre having a vernacular nature and outlook. This paper seeks to examine the spatial impact of informal trading activities on the public space by understanding the background issues in order to evolve a spatial based framework for urban sustainability. To this end, the paper adopts field survey methodology with Isale Eko, Lagos Island as the case study area. The theoretical framework, based on Henri Lefebvre’s spatial triad is the underpinning guide for the field survey. This is supported with Socio-cultural and Linguistic methods in Anthropology to obtain Primary data, which are descriptively presented. Respondents are nominated using stratified random selection, target groups and participants’ observations. Findings reveal that informal trading activities evolve the public space as social space through vernacular and thus, connote socio-cultural expressions in order to ensure livelihood and wellbeing. It further suggests a spatial adaptation strategy to mitigate the challenge of high land use and population density of the island which, from a conventional urban land use perspective, indicates spatial conflict and contestation, hence, a problem. The paper therefore concludes by recommending an inclusive, postmodernism approach which adopts vernacular as a dynamic, sustainable panacea to address urban spatial challenges. DOI: https://doi.org/10.26905/lw.v13i1.5177